Pituitary adenylate cyclase-activating polypeptide mediates bacterial endotoxin-induced fever via an effect on cyclooxygenase-2 and inflammatory cytokines - Jason Sparks; Nora Furedi; Kata Fekete; Margit Solymar; Krisztina Pohoczky; Agnes Kemeny; Dora Reglodi; Andras Garami; Eszter Pakai (Scientific Reports)
Abstract A role for pituitary adenylate cyclase-activating polypeptide (PACAP) signaling was suggested in bacterial lipopolysaccharide (LPS)-induced fever, but the underlying mechanisms of how PACAP contributes to the febrile response have remained unclarified. We administered LPS (120 µg/kg, intraperitoneally) to mice with the Pacap gene either present (Pacap +/+) or absent (Pacap −/− ) and measured their thermoregulatory responses, serum cytokine levels, and tissue cyclooxygenase-2 (COX-2) expression. LPS-induced fever was attenuated in Pacap −/− mice compared to their Pacap +/+ littermates from ~ 120 min postinfusion. LPS increased COX-2 mRNA expression in the lungs, liver, and brain in Pacap +/+ mice at 210 min postinfusion. In the LPS-treated groups, COX-2 mRNA upregulation in Pacap −/− mice was attenuated in the liver, but augmented in the lungs and brain compared to Pacap +/+ mice. In response to LPS, serum concentrations of interleukin (IL)-1α and β were markedly increased in Pacap +/+ mice, but not in Pacap −/− mice, with a significant intergenotype difference between the groups. Serum concentrations of IL-6, IL-10, and TNF-α were higher after LPS treatment compared to saline in both genotypes, however, the rise in IL-10 was significantly attenuted in Pacap −/− mice compared to Pacap +/+ mice. We showed that PACAP contributes to the later phases of LPS-induced fever by modulation of COX-2 expression in the periphery and the brain, as well as by augmentation of circulatory pyrogenic cytokine levels. These findings advance the understanding of the crosstalk between PACAP signaling and the “cytokine-COX-2” axis in systemic inflammation.